Effects of cognitive strategy training on Malaysian tertiary learners' listening comprehension skills in the International English language Testing System test (IELTS) - Shamshiri, Katrin (2010)
The purpose of this study was to look into the effects of cognitive and metacognitive explicit strategy instruction on 56 intermediate level Malaysian college students in listening comprehension. First, the subjects took a pre-test to be randomized in the control and experimental group. Second subjects completed a variety of IELTS listening tasks in 6 weeks. The experimental group received explicit instructions to employ cognitive-metacognitive strategies for 20 minutes every week, while the control group used strategies naturally while completing the tasks without receiving feedback and explicit instruction. Finally, subjects received a post-test. Based on the results of the study, the experimental group outperformed the control group in the post-test, which confirms the positive effects of strategy use and receiving teacher's feedback in previous studies. The effects of task difficulty on using cognitive-metacognitive strategy in IELTS listening test revealed that the experimental group used more cognitive metacognitive strategies for all difficult tasks, while the control group used these strategies for easier tasks or only slightly difficult tasks. In addition, the results supported the positive effects of cognitive-metacognitive strategy training on increasing social and affective strategies during the treatment phase which eventually contributed to the experimental group's better performance in the post-test. Lastly, it was found that while proficiency level may have affected the students' performance, cognitive-metacognitive strategy use was found to have played a more significant role in improving the students' listening comprehension. Finally, the observers' protocol revealed factors such as motivation, personality type, and interaction among the subjects are likely to affect their performance in the listening tasks. Further research is recommended to address these factors and their effect on listening comprehension.